The association of vitamin deficiency with depression risk in late-life depression: a review - Gao, Yao; Song, Xiao-Na; Wen, Zhong-Ping; Hu, Jian-Zhen; Du, Xin-Zhe; Zhang, Ji-Hui; Liu, Sha (Frontiers in Nutrition, 2025)
Late-life depression (LLD), a growing public health challenge in aging societies, profoundly impacts physical and mental health by exacerbating cognitive decline, functional disability, and comorbid chronic diseases. Emerging research highlights vitamin supplementation as a promising adjunctive therapy for LLD, targeting its multifactorial pathogenesis involving mitochondrial dysfunction, neuroinflammation, and oxidative stress. Specific vitamins, including B-complex vitamins (B1, B6, B9, B12), vitamin D, and antioxidants (C, E), demonstrate therapeutic potential through mechanisms ranging from neurotransmitter regulation to mitochondrial function enhancement. For instance, vitamin D modulates serotonin synthesis and calcium signaling, while B vitamins mitigate homocysteine-mediated neurotoxicity and support energy metabolism. Antioxidants counteract neural oxidative damage linked to depressive severity. Clinical studies reveal that vitamin D deficiency (<20 ng/mL) correlates with elevated depression risk, and combined B-vitamin supplementation shows symptom alleviation in nutritionally deficient subgroups. However, evidence remains heterogeneous due to variability in dosing protocols, bioavailability, and population-specific factors like comorbidities. Despite growing evidence, critical gaps persist regarding optimal dosages, bioavailability variations, and long-term outcomes in elderly populations. This review synthesizes current evidence on vitamin-mediated cellular pathways in LLD management, evaluates clinical efficacy across interventions, and proposes personalized nutritional strategies to optimize therapeutic outcomes. By integrating mechanistic insights with clinical data, this analysis aims to guide evidence-based vitamin supplementation protocols for LLD within geriatric care frameworks.